Performance Comparison of Cool, Green, and Black Envelopes in the United States - Chen, Hanjun (Transactions on Engineering and Technology Research, 2024)
As one of the primary sources of greenhouse gas emissions, buildings that need deep decarbonization and passive cooling methods such as cool and green envelopes were regarded as promising solutions. Since previous studies have not comprehensively compared the application of cool roofs, cool walls, green roofs, and green walls in different climate zones in the U.S., this paper aims to fill this gap. Through EnergyPlus 22.1.0 simulation by using the primary school building model from the Department of Energy (DOE), energy savings, cost savings, and emission savings resulting from cool and green envelopes in 9 thermal climate zones are presented. Findings suggest that cool envelopes are more cost-effective with all positive net present values ranging up to 44/m2 from a 40-year life-cycle cost analysis. By contrast, those of green envelopes are all negative. However, green envelopes lead to more energy savings, therefore providing more environmental benefits. In cold climates, such as Fairbanks (8), green roofs and green walls lead to 1.8 kg/m2 and 8.3 kg/m2 of reduction in CO2 emissions, while cool roofs and cool walls result in 0.6 kg/m2 and 1.6 kg/m2 emission savings, respectively. The data also shows generally walls have greater impacts compared to roofs as they benefit multiple floors. By presenting the simulation results, this study will provide a reliable criterion that aids in the selection of some passive cooling methods for building managers in the U.S.